A clinical observational study in cases of eclampsia - Kanani, Bipin; Garala, Nirav J. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Eclampsia is a life threatening condition and one of the leading causes of maternal deaths worldwide. It is also associated with complications like acute renal failure, DIC, postpartum hemorrhage, etc. and adverse fetal outcomes. Hence we aimed to study fetomaternal outcomes in cases of Eclampsia. Methods: A total of 75 cases of eclampsia out of 13524 deliveries were evaluated, from 1st January 2016 to 30th June 2017 at RZ Hospital, a government tertiary referral centre. Maternal outcomes were studied for its complications, effectiveness of magnesium sulphate treatment, fetal outcome and mode of delivery. Results: Incidence rate of eclampsia was 0.55%, 62.66% of all cases were primigravida, 76% of cases were in age group of 21-26 years, 84% cases were from lower socio economic status, maternal mortality occurred in 2 of 75 cases. 66.67% of patients were of term pregnancy (37 to 42 weeks). 71%(53) patients delivered vaginally out of which 9 deliveries were spontaneous and 44 deliveries were induced vaginal delivery. 22 patients required caesarean section. Conclusions: Early detection and prevention of pregnancy induced hypertension and pre-eclampsia and other associated risk factors for eclampsia might help to reduce the incidence of eclampsia. Maternal adverse outcomes in this study were magnesium toxicity, acute renal failure (ARF), disseminated intravascular coagulation (DIC) and post partum hemorrhage (PPH) while 92% patients had no complications.